Academic Self-Efficacy, Achievement Motivation, and Academic Resilience as Predictors of Science Learning Outcomes among Students in the Elementary School Teacher Education Programme - Agung Hastomo; Hendra Setyawan (Postgraduate, University of Mataram, 2026)
Science learning outcomes among elementary school teacher education students are determined not only by mastery of content but also by psychological factors that influence engagement, persistence, and academic success. This study aimed to analyse the effects of academic self-efficacy, achievement motivation, and academic resilience on the science learning outcomes of students in the Elementary School Teacher Education Programme. The study employed a quantitative approach with a correlational survey design. The respondents comprised 136 students. Data were collected through a four-point Likert-scale questionnaire, with 16 items for each variable, and were then analysed using multiple linear regression. Instrument quality indicated that all items were valid and reliable, with Cronbach’s alpha values of 0.951 for academic self-efficacy, 0.953 for achievement motivation, 0.962 for academic resilience, and 0.979 for science learning outcomes. The findings showed that the three predictors simultaneously had a significant effect on science learning outcomes with R = 0.909, R² = 0.826, and F(3,132) = 209.460, p < 0.001. Partially, academic self-efficacy had a significant positive effect, academic resilience emerged as the most dominant predictor, whereas achievement motivation had no significant effect after being controlled together with the other variables. These findings underscore that improving the science learning outcomes of Elementary School Teacher Education students should focus on strengthening academic confidence and learning resilience through challenging, supportive, and sustainable learning experiences.